Circulating B-lymphocytes as potential biomarkers of tuberculosis infection activity. - Ismail Sebina; Irene A Biraro; Hazel M Dockrell; Alison M Elliott; Stephen Cose (PLoS ONE)
Accurate biomarkers of Mycobacterium tuberculosis infection activity would significantly improve early diagnosis, treatment and management of M. tuberculosis infection. We hypothesised that circulating B-lymphocytes may be useful biomarkers of tuberculosis (TB) infection status in highly TB-endemic settings. Ex-vivo and in-vitro mycobacteria-specific B-cell ELISPOT assays were used to examine the plasmablast (PB) and memory B-cell (MBC) responses in the peripheral blood of adult, healthy, community controls (n = 151) and of active TB patients (n = 48) living in Uganda. Frequencies of mycobacteria-specific PBs were markedly higher in active TB patients compared to healthy controls, and, conversely, MBCs were markedly higher in the healthy controls compared to active TB patients. In addition, the community controls with evidence of latent TB infection had higher peripheral blood PB and MBC responses than those without evidence of TB infection. These data demonstrate that peripheral blood B-cell responses are differentially modulated during latent and active M. tuberculosis infection, and suggest that the PB to MBC ratio may be a useful biomarker of TB infection activity.